Porovnání daňového systému v ČR a na Ukrajině - Shyrin, Dmytro (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Bakalářská práce je zaměřena na zobrazení daňových systémů v České republice a na Ukrajině. V teoretické části je řešena charakteristika daňových systémů obou zemí. Praktická část je věnována konkrétním rozdílům mezi daňovými systémy, včetně efektivity daňových sazeb, daňových povinností, odpočtů a slev. Popsány jsou dopady těchto rozdílů na daň z příjmů fyzických osob, osoby samostatně výdělečně činné, náklady zaměstnavatelů na zaměstnance a daň z nemovitých věcí v každé zemi.

The bachelor thesis focuses on depicting the tax systems in the Czech Republic and Ukraine. The theoretical part addresses the characteristics of the tax systems in both countries. The practical part is dedicated to specific differences between the tax systems, including the effectiveness of tax rates, tax obligations, deductions, and exemptions. It describes the impacts of these differences on personal income tax, self-employed individuals, employer costs for employees, and property tax in each country.
Comparison of the tax system in the Czech Republic and Ukraine
Keywords: Česká republika; Ukrajina; daňový systém; efektivnost daní.; Czech Republic; Ukraine; tax system; tax efficiency.